BUDIDAYA MAGGOT (Hermetia illucens) SEBAGAI PAKAN IKAN MAS (Cyprinus carpio) PADA MEDIA TUMBUH APU-APU (Pistia stratiotes) - Angelina Jean Bupu; Yuliana Salosso; Ridwan Tobuku (Universitas Sriwijaya, 2022)
Maggot (Hermetia illucens) is one type of alternative feed from Black Soldier Fly that is easy to cultivate, economical and profitable to reduce the rate of aquaculture production cost. The purpose of this study was to determine the growth of maggot as carp (Cyprinus carpio) feed on the growing medium apu (Pistia stratiotes). Research conducted from March to April 2022, using Complete Randomized Design method with 5 treatments and 3 replications. Treatment composition A = 1 kg dried apu; treatment B = 2 kg dried apu; treatment C = 3 kg dried apu; treatment D = 4 kg dried apu and treatment e = 5 kg dried apu. The result showed the highest maggot population production from treatment B = 1270 population was higher than treatment A, C, D and E with the highest growth weight of carp = 300 grams. The composition from treatment B is 2 kg dried apu, 2 ml probiotics, 4 eggs and 1 kg bran. The results of the ANOVA analysis and BNT test showed that the using P. stratiotes aquatic plants as a living media for maggots had a significant effect on the growth of the population maggot.Key words : Carp feed, Composition, Maggot, Pistia stratiotes